Distribution and risk factors of Ascarididae and other geohelminths in the soil of Uberlandia, Minas Gerais, Brazil - Mota, Kelem Cristina Pereira; Grama, Daliane Faria; Fava, Natália M. Nasser; Úngari, Letícia Pereira; Faria, Elaine Silva Marques; Cury, Márcia Cristina (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Among the geohelminths, parasites from the Ascarididae family have a significant role in the human and animal health. This research aims to determine the prevalence of Ascarididae species in the soil in different areas located in a city of Minas Gerais State, Brazil (South America). The study was developed in squares, parks, sports clubs, orchards and municipal children's schools. Samples of sand/soil/grass were collected from January to August 2014. The optical microscope screening was performed through formal-ether and spontaneous sedimentation techniques. Out of the 183 collected samples, eight (4.4%) belonged to parks, 16 (8.7%) to sports clubs, 76 (41.5%) to squares, 23 (12.6%) to orchards, and 60 (32.8%) to schools. Out of the total, 28 (15.3%) contained Ascarididae eggs. Higher levels of positivity were demonstrated in the raining season (25.0%), in samples collected in the southern region of the town (25.1%), on ground soils (27.3%). Twenty-three (12.6%) were detected by the formal-ether sedimentation technique and 10 (5.5%) by spontaneous sedimentation technique. Therefore, it was concluded that the soils in the city of Uberlandia are contaminated with eggs and larvae of geohelminths, enabling dissemination of illnesses among animals and human beings.